(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Evaluation of anti-fungal activity 14 different phytoextracts against Sclerotium rolfsii causing Wilt disease in Sunflower was tested in-vitro conditions. The plants selected for this study were Syzgium aromaticum, Cinnamomum verum, Piper nigrum, Phyllanthus emblica, Calotropis procera, Nerium oleander, Psidium guajava, Eucalyptus globulus, Citrus limon, Lawsonia inermis, Zingiber officinale, Allium sativum, Allium cepa and Azadirachta indica. Aqueous extracts of these plants Syzgium aromaticum, Cinnamomum verum, Piper nigrum, Phyllanthus emblica and Allium sativum showed 100% growth inhibition of the pathogen at 20% concentration.